(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The pandemic has made online shopping more popular as people prefer to shop online rather than buy at a physical store to avoid getting infected by the virus. This study aims to determine the satisfaction of online shopping platforms for ABM students. Furthermore, results showed that the proposed output of satisfaction on online shopping platforms would help online businesses to improve and to be recognized in terms of spending less on the product and service’s cost, wider range and easier distribution of service, and satisfy the necessities and demands of their customers with the use of online shopping platforms. Respondents need to be aware of what they purchase online that may satisfy them. Online shopping platforms that they need to use are trusted and convenient platforms for them to choose the right products. Consumers need to know about the products they will purchase online.